2009
DOI: 10.1136/bjo.2008.148122
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular pressures after ketamine and sevoflurane in children with glaucoma undergoing examination under anaesthesia

Abstract: Sevoflurane lowers the IOP significantly compared with the IOP measured after ketamine. This difference is independent of the IOP level. It may be important to use ketamine as the induction anaesthetic agent when accurate IOP measurement is necessary during EUA for children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 19 publications
0
9
0
4
Order By: Relevance
“…With regards to measurements taken under CH sedation, the drug appears to leave the IOP levels unaltered, in contrast to the case for general anaesthetic medications 16 20 21. In electrodiagnostics, it was shown that CH reduces the amplitude of the a- and b-waves of scotopic bright-flash ERG recordings, without affecting implicit times, while anaesthesia (halothane or isoflurane, in combination with N 2 O) reduced the amplitude and prolonged the implicit times of photopic ERG 14.…”
Section: Resultsmentioning
confidence: 98%
“…With regards to measurements taken under CH sedation, the drug appears to leave the IOP levels unaltered, in contrast to the case for general anaesthetic medications 16 20 21. In electrodiagnostics, it was shown that CH reduces the amplitude of the a- and b-waves of scotopic bright-flash ERG recordings, without affecting implicit times, while anaesthesia (halothane or isoflurane, in combination with N 2 O) reduced the amplitude and prolonged the implicit times of photopic ERG 14.…”
Section: Resultsmentioning
confidence: 98%
“…Multiple measurements (at least 3) were made until consistent readings were obtained after the initial IOP spike that was observed in some patients. 8 Success was defined as postoperative IOP between 6 and 22 mm Hg and an IOP reduction of at least 20% from preoperative levels without (complete success) or with (qualified success) topical and/or oral antiglaucoma medications. Additional criteria for success included no devastating vision loss and no need for additional glaucoma surgery including cyclodestructive procedures; however, interventions to improve function of the GDD (such as repositioning/shortening of tube or adjustment/removal of the stent suture) were allowed.…”
Section: Methodsmentioning
confidence: 99%
“…[11] In order to overcome these shortcomings, we recommend that health practitioners in a country such as Nigeria further explore the use of ketamine anesthesia for pediatric ophthalmic surgery. Even in settings where cost consideration is not a major constraint, ketamine when used alone [12] or as the induction anesthetic agent, [13] has a distinctive advantage in not falsely lowering intraocular pressures as most other anesthetic agents do. The study of Pun et al [14] in which they found the use of ketamine anesthesia in a consecutive series of 679 Nepalese children to be safe and effective needs to be further explored as a nonanesthetist with some training in resuscitative procedure administered the drug.…”
Section: Discussionmentioning
confidence: 99%